Self-Care Behaviour Practices and Associated Factors Among Adult Hypertensive Patient in Padang - Gusty, Reni Prima; Merdawati, Leni (University of Muhammadiyah Malang, 2020)
Introduction: Hypertension self-care practice is essential for blood pressure control and reduction of hypertension complications. An Assessment of an individual hypertension self-care behavior may provide clinicians and practitioners with important information regarding how to control hypertension. Objective: The purpose of this study was to assess Hypertension self-care practice and associated factors among patients in public health facilities in Padang. Method: In this cross-sectional study design with proportional random sampling. 260 hypertensive patients. Self-care activities were measured using hypertension self-care activity level effects (H-Scale). Results: The mean age was 60 years old, women (65.8%), unemployed (88.1%), senior high school (47.7%), duration had hypertension for 5-10 years (49.6%). 67.3% normal body mass index, 83.5% nonsmoking, 72.3% hadâ€™ not central obesity. There were four components of self-care that had a low level. They were physical activity adherence, using a low salt diet, weight management, and medication adherence. 100% abstinence from alcohol, 73.8% nonsmoking. The results of Chi-square indicated that BMI (p=0.002), central obesity (p = 0,000) wereÂ significantly associated with treatment adherence; there were also a significant association between education (p=0.005), BMI (p=0.002) and central obesity (p=0,000) with diet adherence; the age (p = 0.008), education (p = 0.014) and central obesity (p = 0,000) with adherence to physical activity; sex (p = 0,000), work (p=0,000) and education (p=0.025) with nonsmoking. Discussion: It is crucial to implement a well- designed program to improve hypertension self-care behaviors.